2015
DOI: 10.1007/s10298-015-0936-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition chimique d’Ammi visnaga L. (Lam.) marocaine et activité antibactérienne de son huile essentielle vis-à-vis de bactéries productrices et non productrices de beta-lactamases à spectre élargi

Abstract: Composition chimique d'Ammi visnaga L. (Lam.) marocaine et activité antibactérienne de son huile essentielle vis-à-vis de bactéries productrices et non productrices de beta-lactamases à spectre élargi Chemical composition of Moroccan Ammi visnaga L. (Lam.) and antibacterial activity of its essential oil against extended-spectrum beta-lactamase-producing and not producing bacteria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…For L. pedunculata, SORO et al [27] obtained a yield of 1,97% that is slightly higher than our result. These variations in EO yields can be explained by several factors including the degree of maturity of the flowers, the interaction with the environment (type of climate, soil), the time of harvest and the extraction method [28].…”
Section: Table1: Essential Oils' Yields Of Selected Lavenderscontrasting
confidence: 83%
“…For L. pedunculata, SORO et al [27] obtained a yield of 1,97% that is slightly higher than our result. These variations in EO yields can be explained by several factors including the degree of maturity of the flowers, the interaction with the environment (type of climate, soil), the time of harvest and the extraction method [28].…”
Section: Table1: Essential Oils' Yields Of Selected Lavenderscontrasting
confidence: 83%
“…The chemical constituents of the essential oils of A. visnaga are distributed mainly among the following groups: nonterpenes and monoterpenes [24], in addition to diterpenes and sesquiterpenes but only in very small amounts in the case of the latter two [25]. The most abundant constituents of A. visnaga essential oils were found to be isoamyl 2-methylbutyrate, isoamyl isobutyrate, iso-butyl-2-methylbutyrate, 2-methylbutyl 2-methylbutyrate, 2-methylbutyl isobutyrate, and isoamyl isovalerate [14,26]. A large group of the volatiles identified in A. visnaga belong to the monoterpenes class.…”
Section: Essential Oilmentioning
confidence: 99%
“…Moreover, the same extract revealed antimicrobial activity against the Gram-negative bacteria Escherichia coli and Klebsiella pneumoniae [77]. Several studies have focused on the antimicrobial effects of the essential oils of the A. visnaga L., showing their effectiveness against various microorganisms such as Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae strains [25,26,78,79]; however, they showed weak antifungal activities [34]. Razzaghi-Abyaneh identified components that strongly inhibited aflatoxin formation in toxigenic fungi, e.g., khellin, xanthotoxin, and bergapten [20].…”
Section: Several Studies Have Reported On the Antimicrobial Effects Of The Different Extracts Of Avisnagamentioning
confidence: 99%
“…In addition to khellinin, khellinone, and visnaginone [ 10 ], other significant γ-pyrones are 5,7-dihydroxy-2-methyl-γ-pyrone-7-O-glucoside [ 12 ]. The most prevalent components of A. visnaga essential oils were also discovered to be isoamyl 2-methylbutyrate, isoamyl isobutyrate, iso-butyl-2-methylbutyrate, 2-methylbutyl 2-methylbutyrate, 2-methylbutyl isobutyrate, and isoamyl isovalerate [ 45 , 47 ]. Our study involved the analysis of various phytochemical compounds using GC-MS. Docosanolide (73.39%) was identified as the main photochemical component in the obtained methanol extract of roots.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have conducted investigations on the antibacterial activities of A. visnaga L. essential oils, and their effectiveness against various pathogens has been demonstrated. These studies have shown that A. visnaga L. essential oils exhibit notable efficacy against pathogens such as E. coli , P. aeruginosa, and K. pneumoniae strains [ 20 , 47 , 70 ].…”
Section: Discussionmentioning
confidence: 99%